Gene Location for Molybdenum Cofactor Deficiency - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Linkage of a molybdenum cofactor deficiency (MoCoD) gene to an 8-cM region on chromosome 6p21.3 has been localized by homozygosity mapping in 2 consanguineous affected kindreds of Israeli-Arab origin, including 5 patients, at the Department of Genetics, Tamkin Research Facility, Technion-Israel Institute of Technology, Haifa, Israel.